Prescription Auditing and Study of Drug Utilization Pattern in Outpatient Pharmacy of a Tertiary Care Hospital, Bengaluru, India - Nourmand, Niloufar (Asian Journal of Pharmaceutics (AJP), 2019)
Background: Drugs play an important role in disease prevention and health-care delivery. The availability and affordability of good quality drugs along with their rational use are required for effective health care. Prescription audit is one of the important components of clinical pharmacy, where clinical pharmacist plays an important role in optimization of medication use, minimizing number of medication-related problems and improving medication therapy. Objective: The main objective of the present study was to perform a prescription audit and detect prescription related errors and rationality of prescription. Materials and Methods: This prospective observational study carried out for 6 months in the Department of Pharmacy practice, Karnataka College of Pharmacy, Bangalore Baptist Hospital. The study result shows that majority of patients was female. Moreover, adults between the age group of 20- and 60-yearold were highly affected of patient. Major diagnosis was infection followed by diabetes mellitus and hypertension. It was concluded that almost 33% prescribed drugs were not written in generic name followed by drugs not in capital and without direction type of errors. The most prescribed drug category was antipyretics, followed by antibiotics and antidiabetic I t was noted that two drugs such as ofloxacin eye drops and pregabalin topical cream presenting formulary were prescribed in study patient. The most prescribed drug was paracetamol followed by aspirin and pantoprazole Conclusion: It was found that almost quarter of drugs prescribed were belonged to high-risk medication group. Antidiabetics were highly prescribed drug category of high-risk medication. Drugs majorly prescribed were in tablet and syrup form. The study shows few drug interactions compared to population size, and the drugs involved were aspirin, clopidogrel, ciprofloxacin, carvedilol, and glimepiride.